Peran Bank Syariah Dalam Pengembangan Wisata Halal Di Aceh (Studi Kasus Bank Aceh) - Ririn Sari Mawar Dani (Yayasan Rahmat Islamiyah, 2022)
Halal tourism includes halal food, halal drinks, halal UMKM, mosques, and facilities that provide services for the convenience of worship. Therefore, this study aims to determine the role given by Islamic banks, namely Aceh banks, to the development of halal tourism in the vicinity. The research method used by the author for this research is a qualitative research method by interviewing two informants who are employees of the Aceh bank in the financing section. The results obtained after conducting this research is the role given by the Aceh bank in the development of halal tourism in the vicinity is to provide financing with a murabahah contract. Where, the bank as a provider of funds to be given to business sector actors who need funds for business development. The financing scheme with a murabahah contract is that the bank and the customer negotiate to reach a financing agreement, the financing that is approved by the bank, the customer has two options to give the bank the right to purchase business needs or to shop on their own by conducting a wakalah contract as a complementary contract to the financing of the murabahah contract.